Pengaruh pre-cooling dan Suhu Simpan terhadap Kualitas Pascapanen Tanaman Gonda (Sphenoclea zeylanica Gaertn) - TAMPUBOLON, MIRNASEN; SUKEWIJAYA, I MADE; GUNADI, I GUSTI ALIT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.2, April 2017, 2017)
The Effects Of Pre-Cooling and Controlled Temperature On The Crop Quality Of Post-Harvested Gonda (Sphenoclea Zeylanica Gaertn) The Gonda plant (Sphenoclea zeylanica Gaertn) is highly prized by the Balinese people, and so, is always readily available, and can be found in both Traditional Balinese markets and modern supermarkets. The Gonda leaf has high-nutritional value, and is widely consumed for this quality. The farming community hasn’t adapted better post-harvesting treatments to maintain the produce’s qualities. What is needed is a treatment-system that consistently maintains the harvested Gonda at different temperatures (pre-cooling). This study aims to determine the effects of pre-cooling and temperature on post-harvested Gonda stores. This research was conducted by Pacsapanen Technology Laboratory, Faculty of Agriculture, University of Udayana. The study applied the Randomized Block Method (RAK), which consists of: P0, P1 through a combination of: S1, S2, and S3. There were 6 combinations of treatments that were repeated 4 times. The results show that the effects of pre-cooling combined with temperature treatment are the least statistically significant (P ? 0,05) on all observed variables. Pre-cooling (P) alone had significant impact on variables (P> 0.05), affecting chlorophyll, weight loss, shelf life, and CO2 respiration rate (ml / g / h), while temperature treatment alone also significantly affected chlorophyll, weight loss, shelf life, and O2 respiration rate variables (ml / g / h). We conclude that low-temperature storage (7C-10C) is the most effective method to maintain the quality of post-harvested Gonda.